COMPARATIVE TREATMENT OF WELL AND STREAM WAGTER FOR DRINKING USING MORINGA OLEIFERA SEEDS, ALUM, SAND FILTER BEDS AND SOLAR RADIATION - Ikechukwu Benjamin, MOSES; Babatunde, Awopetu; Odeyemi, Olu (International Journal of Tropical Medicine and Public Health, 2020)
International Journal of Tropical Medicine and Public Health,Vol.1, Issue 1, p.8